Frontiers of Intelligent Autonomous Systems - Lee, Sukhan; Yoon, Kwang-Joon.; Lee, Jangmyung; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This carefully edited volume aims at providing readers with the most recent progress on intelligent autonomous systems, with its particular emphasis on intelligent autonomous ground, aerial and underwater vehicles as well as service robots for home and healthcare under the context of the aforementioned convergence. (3z(BFrontiers of Intelligent Autonomous Systems(3y (Bincludes thoroughly revised and extended papers selected from the 12th International Conference on Intelligent Autonomous Systems (IAS-12), held in Jeju, Korea, June 26-29, 2012. The editors chose 35 papers out of the 202 papers presented at IAS-12 which are organized into three chapters: Chapter 1 is dedicated to autonomous navigation and mobile manipulation, Chapter 2 to unmanned aerial and underwater vehicles and Chapter 3 to service robots for home and healthcare. To help the readers to easily access this volume, each chapter starts with a chapter summary introduced by one of the editors: Chapter 1 by Sukhan Lee, Chapter 2 by Kwang Joon Yoon and Chapter 3 by Jangmyung Lee.s
Chapter I Autonomous Navigation and Mobile Manipulation -- Chapter II Unmanned Aerial and Underwater Vehicles -- Chapter III Service Robots for Home and Healthcare.
Keywords: Engineering; Artificial intelligence; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).